Astragaloside IV alleviates inflammation and improves myocardial metabolism in heart failure mice with preserved ejection fraction - Wang, Xiao; Chen, Xinting; Wang, Yuting; He, Xinyu; Li, Lan; Wang, Xiaodan; Huang, Yuting; Fan, Guanwei; Ni, Jingyu (Frontiers in Pharmacology, 2024)
Background: Heart failure with preserved ejection fraction (HFpEF) has grown to become the dominant form of heart failure worldwide. However, no unequivocally effective treatment for HFpEF has been identified in clinical trials. In this study, we report that Astragaloside IV (AS-IV) can be used to treat HFpEF.Methods: Mice were fed on a high-fat diet and given 0.5 g/L L-NAME (in drinking water) for 10 weeks to establish the HFpEF model. After 10th weeks, the HFpEF mice were given 10 mg/kg empagliflozin, 10 mg/kg AS-IV, or 20 mg/kg AS-IV for four weeks. The echocardiography, blood pressure, hemodynamics, heart failure biomarkers, collagen deposition and fibrosis, histopathology, and inflammation in HFpEF mice were evaluated. Metabolic profiling based on NMR measurements was also performed. Myocardial glucose and fatty acid metabolism were evaluated.attenuates systemic inflammatory infiltration and myocardial inflammation levels in HFpEF mice by decreasing the expression of plasma inflammatory markers GDF15, CRP, IL1RL1, and MCP-1, NLRP3, IL-1β, Caspase-1, and IL-6 in the myocardium of HFpEF mice. Metabolomic analysis suggested that AS-IV improved cardiac glucose and fatty acid metabolism in HFpEF mice. Further studies showed that AS-IV significantly improved Complex I activity, increased ATP production, and elevated plasma NAD+ levels; AS-IV also significantly improved pyruvate dehydrogenase activity and decreased pyruvate and lactate accumulation, thereby improving glucose metabolism in the hearts of HFpEF mice.